EVALUASI KEKUATAN DAN STRUKTUR MIKRO SAMBUNGAN LAS TIG PADA PIPA ZIRCONIUM - Bandriyana, B.; Sibarani, Maradu (Industrial and Systems Engineering Assessment Journal (INASEA), 2010)
Welded joints of the zirconium pipe were widely used in the chemical industry or nuclear facility because their high mechanical properties and high corrosion resistance of zirconium material. To improve the mechanical properties of welded joint a method of TIG (Tungsten Inert Gas) welding with a suitable welding parameters were necessary used. Evaluation of strength and microstructure of the welded joint will be used to improve the quality, strength and process technology. This paper described the evaluation of the hardness, strength and microstructure of the TIG welded joint of Zircalloy- 2 pipe. The welding was done for two kinds of samples using the welding machine of the M80-3 model of the TIG (Tungsten Inert Gas) type, with the welding current of 30 and 35 Ampere/ second respectively. The hardness test was done by using the Vickers hardness scale. Testing of welded joint strength was carried out using the hydrostatic test by measured the change of pipe diameters and observed the pipe brake according to the internal pressure of 100, 200, 400 and 425 bars given into the pipe, and the microstructure test was observed by using the optical microscope. The hardness test showed that the maximum hardness number of 203 VHN was occurred at the heat affected zone (HAZ) area obtained. The result of hydrostatic test showed that there was not a change on the dimensions in the welded area up to internal pressure test of 400 bars.